PS2-10: Predictors of Depression and Poor Physical Health among Patients with Chronic Hepatitis C Infection: Results from the Chronic Hepatitis Cohort Study - Boscarino, Joseph (Clin Med Res, 2014)
BACKGROUND/AIMS: Our objective was to assess risk factors for depression and poor physical health among patients with chronic hepatitis C virus (HCV) infection. METHODS: We conducted a survey of HCV patients seen at 4 large healthcare systems with laboratory-confirmed HCV. A total of 4,781 patients completed surveys in 2011–2012 (completion rate = 60%). Survey data included demographics, PHQ-8 depression, SF-8 physical health, level of social support, stress exposures, and from the medical record, HCV treatment history and the Charlson comorbidity score. RESULTS: The mean age of patients was 57 (SD = 18), 71% (95% CI = 70–72) were Caucasian, 57% (95% CI = 56–58) male, 47% (95% CI = 46–49) had been treated for HCV, 51% (95% CI = 50–53) reported past injection drug use, 60% were HCV genotype 1, and 15% (95% CI = 14–15) had confirmed sustained viral response (SVR) to HCV therapy. Altogether, 30% of patients (95% CI = 28–31) met criteria for current depression on the PHQ-8 and 25% (95% C = 23–26) had poor physical health on SF-8. In multivariate logistic analyses, the best predictors of depression included female gender (OR = 1.34, P <0.001) age (OR = 0.83, P <0.001), Caucasian race (OR = 1.42, P <0.001), unemployment (OR = 2.98, P <0.001), high stressor exposure vs. low (OR = 2.61, P <0.001), low social support vs. high (OR = 1.73, P <0.001), history of drug rehabilitation (OR = 1.45, P <0.001), and higher Charlson comorbidity scores (OR = 1.17, P <0.001). Having SVR to HCV therapy, was protective for depression (OR = 0.77. P = 0.017). The best predictors of poor physical health included Caucasian race (OR = 1.46, P <0.001), unemployment (OR = 3.96, P <0.001), higher Charlson scores (OR = 1.28, P <0.001), high stressor exposure vs. low (OR = 1.78, P <0.001), and moderate social support vs. low (OR = 1.48, P <0.001). Counter to expectation, injection drug use history was protective of poor physical health (OR = 0.71, P < 0.001). CONCLUSIONS: Among HCV patients, the best predictors of depression and poor physical health were demographic factors, employment status, Charlson scores, current life stressors, and current social support. While SVR was protective for depression, HCV treatment history was generally not associated with mental health or physical health status, once other covariates were controlled.